2014
DOI: 10.1039/c3cs60328h
|View full text |Cite
|
Sign up to set email alerts
|

The role of isovalency in the reactions of the cyano (CN), boron monoxide (BO), silicon nitride (SiN), and ethynyl (C2H) radicals with unsaturated hydrocarbons acetylene (C2H2) and ethylene (C2H4)

Abstract: The classification of chemical reactions based on shared characteristics is at the heart of the chemical sciences, and is well exemplified by Langmuir's concept of isovalency, in which 'two molecular entities with the same number of valence electrons have similar chemistries'. Within this account we further investigate the ramifications of the isovalency of four radicals with the same X(2)Σ(+) electronic structure - cyano (CN), boron monoxide (BO), silicon nitride (SiN), and ethynyl (C2H), and their reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Computational studies on the reaction mechanism have indicated that there are two plausible channels from the direct CN + C 2 H 4 addition intermediate, the CH 2 CH 2 CN radical: 106,107 The photoionization spectrum of the m/z 53 product shows no evidence for the production of the isocyanoethene (CH 2 CH-N=C) species as the AIE of this isomer is calculated (CBS-QB3) to be 10.56 eV and no ion signal is detected until 10.9 eV. Calculations are in agreement with this finding, revealing that the H-elimination transition state from a CH 2 CH 2 NC is placed +12 kJ mol -1 above the entrance channel energy of the reactants.…”
Section: Methodsmentioning
confidence: 99%
“…Computational studies on the reaction mechanism have indicated that there are two plausible channels from the direct CN + C 2 H 4 addition intermediate, the CH 2 CH 2 CN radical: 106,107 The photoionization spectrum of the m/z 53 product shows no evidence for the production of the isocyanoethene (CH 2 CH-N=C) species as the AIE of this isomer is calculated (CBS-QB3) to be 10.56 eV and no ion signal is detected until 10.9 eV. Calculations are in agreement with this finding, revealing that the H-elimination transition state from a CH 2 CH 2 NC is placed +12 kJ mol -1 above the entrance channel energy of the reactants.…”
Section: Methodsmentioning
confidence: 99%
“…This is well reflected in the difference in chemical bonding of the c-SiC 2 molecule, which exhibits a cyclic C 2v symmetric structure, while the tricarbon (C 3 ) molecule is (quasi)linear at its ground state molecular geometry. Similarly, the isovalent cyano (CN) and silicon nitride (SiN) radicals revealed significant discrepancies in reactivity with unsaturated hydrocarbons such as acetylene (C 2 H 2 ) and ethylene (C 2 H 4 ), by bonding the carbon in the cyano (CN) and nitrogen in the silicon nitride (SiN) to the unsaturated hydrocarbons [12][13][14][15][16][17]. Considering the title reaction, the diverse chemical bonding of silicon analogous species is also evident, when comparing the silylidyne-acetylene (SiH-C 2 H 2 ) and methylidyne-acetylene (CH-C 2 H 2 ) potential energy surfaces (PESs) [18,19] as well as the cyclopropenylidene (c-CC 2 H 2 ) and silacyclopropenylidene (c-SiC 2 H 2 ) isomers in particular [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Which experimental approach can best reveal the chemical dynamics involved in the formation of PAHs in the gas phase? Experiments conducted under single-collision conditions, in which particles A of one supersonic beam are made to collide only with particles BC of a second beam (Equation 1), are ideal to investigate the chemical dynamics of bimolecular gas phase reactions at the most fundamental, microscopic level (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). These are crossed molecular beam experiments.…”
Section: The Crossed Molecular Beam Approachmentioning
confidence: 99%